2021
DOI: 10.1186/s13027-021-00369-0
|View full text |Cite
|
Sign up to set email alerts
|

Lung histopathological findings in COVID-19 disease – a systematic review

Abstract: Since December 2019, the global burden of the COVID-19 pandemic has increased rapidly and has impacted nearly every country in the world, affecting those who are elderly or with underlying comorbidities or immunocompromised states. Aim of this systematic review is to summarize lung histopathological characteristics of COVID-19, not only for diagnostic purpose but also to evaluate changes that can reflect pathophysiological pathways that can inform clinicians of useful treatment strategies. We identified follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 128 publications
(353 reference statements)
3
36
0
3
Order By: Relevance
“…During the mechanism of dysfunction of the alveolar epitheliums, important roles are related to alveolar epithelial cells type I/II (AEI/AEII). AEII coordinates the host defense mechanisms, not only generating the restrictive alveolar epithelial barrier, but also secreting pulmonary surfactant, which reduces surface tension at the pulmonary air-liquid interface, thereby preventing atelectasis and alveolar edema [10][11][12][13][14]. Furthermore, the innate immune responses to infection of AEII lead both to the cell death by pyroptosis and apoptosis and to the activation alveolar macrophages [10][11][12][13][14].…”
Section: Endothelial Injuries In Covid-19mentioning
confidence: 99%
See 2 more Smart Citations
“…During the mechanism of dysfunction of the alveolar epitheliums, important roles are related to alveolar epithelial cells type I/II (AEI/AEII). AEII coordinates the host defense mechanisms, not only generating the restrictive alveolar epithelial barrier, but also secreting pulmonary surfactant, which reduces surface tension at the pulmonary air-liquid interface, thereby preventing atelectasis and alveolar edema [10][11][12][13][14]. Furthermore, the innate immune responses to infection of AEII lead both to the cell death by pyroptosis and apoptosis and to the activation alveolar macrophages [10][11][12][13][14].…”
Section: Endothelial Injuries In Covid-19mentioning
confidence: 99%
“…AEII coordinates the host defense mechanisms, not only generating the restrictive alveolar epithelial barrier, but also secreting pulmonary surfactant, which reduces surface tension at the pulmonary air-liquid interface, thereby preventing atelectasis and alveolar edema [10][11][12][13][14]. Furthermore, the innate immune responses to infection of AEII lead both to the cell death by pyroptosis and apoptosis and to the activation alveolar macrophages [10][11][12][13][14]. In addition, the glucocorticoid receptor α acts as a cellular rheostat to ensure that a proper response is elicited by the neuro-endocrine and immune systems [6,15].…”
Section: Endothelial Injuries In Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…A histopathological study of changes in COVID-19 related lung disease revealed several changes from normal lung tissue, including damage to endothelial cell and epithelial/alveolar cells (Pannone et al, 2021). Endothelial alterations in COVID-19 include a hypercoagulability due to increased factor VIII and von Willebrand factor (Escher et al, 2020;Pannone et al, 2021). Additionally, there are elevated levels of plasma angiotensin II in COVID-19 patients.…”
Section: Pulmonary Epithelial and Endothelial Damagementioning
confidence: 99%
“…Additionally, there are elevated levels of plasma angiotensin II in COVID-19 patients. Angiotensin II can lead to vascular permeability and further endothelial damage (Liu et al, 2020b;Pannone et al, 2021). The aggressive production of pro-inflammatory cytokines such as IL-6 and TNF-α disrupts normal anti-thrombotic and anti-inflammatory function of the endothelium, which can cause dysregulated complement activation (Pannone et al, 2021).…”
Section: Pulmonary Epithelial and Endothelial Damagementioning
confidence: 99%